The Correlation Between Biology Learning Outcomes and Senior High School Students’ Self Concept - Rodiah, Siti; Komala, Ratna; Rusdi, Rusdi (Jurnal Penelitian dan Pembelajaran IPA, 2020)
This study aimed to understand the correlation between academic self-concept and biology learning outcomes on high school students at virus material. The design used in this study was correlational. This study used descriptive quantitative as its method. The subjects of this study were tenth-grade students of senior high school in Tangerang Regency. The subjects of this study consisted of 135 respondents men and women, there were 102 respondents were taken as the sample through a simple random sampling technique. The data were obtained using the instrument of academic self-concept and students' learning outcomes on virus material. The learning outcomes were based on the multiple-choice test. After that, the obtained data were analyzed using Pearson Product Moment (PPM) of the SPSS 16 version. The results show that there is a positive and significant correlation between academic self-concept and biology learning outcomes of students with the coefficiency (rx1y) of 0.553